Pelatihan Pengelolaan Sampah Organik dengan Smart Sensor kepada Office Boy - Dwi Indah Suryani; Sulaeman Deni Ramdani; Mudmainah Vitasari; Moch Fawaid (Universitas Mathla'ul Anwar Banten, 2021)
ORGANIC WASTE MANAGEMENT TRAINING WITH SMART SENSORS FOR OFFICE BOY. Organic waste is a type of waste that can cause pollution both in the air and in the soil environment. Based on observations in the field, organic waste is only disposed of in the trash and mixed with inorganic waste before being carried by a garbage truck. So, an alternative solution is needed, namely training in organic waste management with smart sensors for Office Boy (OB) in the FKIP Untirta environment. The aim of this community service activity is to train OB in making trash bins with smart sensors and processing organic waste to become economically valuable products. The results of this recycling can be used as fertilizer for plants in the FKIP Untirta environment so that it supports the concept of Untirta's Green Campus. This activity is in the form of training using practical methods. The implementing team provides materials and guides the practice of making trash bins and processing waste. In addition, the participants carried out the practice provided with manual books to facilitate the training process. Participants who took part were all OB from the FKIP environment totaling 26 people. The data obtained by this training activity used a questionnaire and performance. Based on the results of the questionnaire data analysis of the participant's satisfaction with community service activities in the form of organic waste management training with smart sensors to Office Boy at FKIP Untirta, for indicators of activity effectiveness, criteria are very effective and for team performance indicators, criteria are very effective.